ENGLISH LEARNING STRATEGY BY APPLYING CR STRATEGY FOR ESP CLASS - A. Samsu Rijal (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
ESP Students of Makassar Islamic University cannot be acquired the four language skills simultaneously since they are still low vocabulary achievement. This research aimed at investigating whether the contextual redefinition (CR) strategy could improve the ESP students’ vocabulary achievement. This research was pure experimental research which carried out in the pharmacy Department of Makassar Islamic University as the one ESP class. Whereas the CR strategy was taught in the treatment group. To find out the improvement of students’ vocabulary achievement, the researcher used pre-test and post-test. Then data were analysed by using SPSS and t-test. The research result indicates, that the procedure in the application of contextual redefinition strategy can lead students to be independent learners inside and outside of the class. Their terminological knowledge improve well after they were taught contextual redefinition as available strategy to unlock the meaning of unknown words from the pharmacy literature. Statistically, the mean score for pre test is 36.7667, and the mean score for the post test is 54.1467. this means that the vocabulary teaching through contextual redefinition strategy significantly has the impact on pharmacy students’ vocabulary achievement. Since the application of this strategy the pharmacy students give positive attitude there are 73.3 % of pharmacy students who agree if the English teachers for the Pharmacy English use the strategy to improve the students’ vocabulary. The use of contextual redefinition strategy in vocabulary teaching can have the positive impact on the development of the pharmacy students’ vocabulary achievement.